Inflammatory cytokines promote interferon regulatory factor (IRF) transcriptional activity in human pulmonary epithelial cells through the induction of IRF1 by nuclear factor-κB - Amandah Necker-Brown; Mahmoud M. Mostafa; Andrei Georgescu; Andrew J. Thorne; Priyanka Chandramohan; Cora Kooi; Keerthana Kalyanaraman; Alex Gao; Akanksha Bansal; Sarah K. Sasse; Anthony N. Gerber; Richard Leigh; et al. (PLoS ONE, 2025)
Interferon regulatory factors (IRFs) play key roles during viral and bacterial infections. However, their regulation by inflammatory cytokines, including interleukin (IL)-1β and tumor necrosis factor (TNF) α, remains underexplored. As airway epithelial cells (AECs) modulate lung inflammation, IRF expression was characterized in pulmonary A549 and bronchial BEAS-2B epithelial cells along with primary AECs grown in submersion, or air-liquid interface, culture. While, IRF6 mRNA was only highly expressed in primary cells, IRF4 and IRF8 mRNAs were consistently low across the models. All the other IRF mRNAs were expressed in each model. IRF3 and IRF9 mRNAs were highly expressed, but their proteins remained primarily cytoplasmic post-IL-1β treatment in A549 cells. IRF2 showed moderate/high mRNA expression and was constitutively nuclear. However, RNA silencing did not support roles for IRF2 or IRF3, with only a modest role for IRF9, in the IL-1β-induced activation of an IRF reporter. IRF1 mRNA was highly induced by IL-1β in A549 and primary cells. Similarly, IRF1 protein was increased by IL-1β and TNFα in A549 cells, and by TNFα in BEAS-2B cells. In A549 cells, IL-1β-induced IRF1 protein localized to the nucleus and since IRF1 silencing prevented IRF reporter activity, a major transcriptional role was indicated. Mechanistically, the inflammatory transcription factor, nuclear factor (NF)-κB, was necessary for IL-1β- and TNFα-induced IRF1 expression. Further, four novel enhancer regions 5′ to IRF1 bound the NF-κB subunit, p65, and their IL-1β/TNFα-induced reporter activity required consensus NF-κB motifs. Three such regions recruited RNA polymerase-2 and were flanked by the active chromatin mark, histone 3 lysine 27 acetylation, supporting enhancer involvement in IRF1 transcription. Finally, IRF1 expression, transcription rate, and enhancer activity induced by IL-1β, or TNFα, were relatively unaffected by glucocorticoid. IRF1-dependent gene expression may therefore show insensitivity to glucocorticoid and could contribute to glucocorticoid-resistance in diseases that include severe asthma.